The Pythagorean Theorem:

\(\displaystyle{a}^{{2}}+{b}^{{2}}={c}^{{2}}\)

Where a and b are cathetuses and c is the hypothenuse. Substitute from the given:

\(\displaystyle{c}^{{2}}={1}^{{2}}+{\left(\sqrt{{3}}\right)}^{{2}}\)

\(\displaystyle{c}=\sqrt{{{1}+{3}}}\)

\(\displaystyle{c}=\sqrt{{4}}\)

c=2

The hypothenuse's length is 2cm.

\(\displaystyle{a}^{{2}}+{b}^{{2}}={c}^{{2}}\)

Where a and b are cathetuses and c is the hypothenuse. Substitute from the given:

\(\displaystyle{c}^{{2}}={1}^{{2}}+{\left(\sqrt{{3}}\right)}^{{2}}\)

\(\displaystyle{c}=\sqrt{{{1}+{3}}}\)

\(\displaystyle{c}=\sqrt{{4}}\)

c=2

The hypothenuse's length is 2cm.